THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN FORMING CHARACTER STUDENTS IN SCHOOLS - Hasanah, Ismiyatun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to find out: 1) To find out the implementation of Islamic Religious Education in schools, 2) To know and understand the role of Islamic religious education in shaping students' character in schools, 3). To find out the different levels of the role of Islamic religious education in shaping students' character in schools. This research uses quantitative, factual, and accurate research by making questionnaires to respondents who will answer statements about the role of Islamic religious education in shaping students' character in schools.